Analyzing protein–protein interactions in rare cells using microbead-based single-molecule pulldown assay. Issue 16 (24th June 2021) - Zhao, Qirui; Shen, Yusheng; Li, Xiaofen; Tian, Fang; Yu, Xiaojie; Yobas, Levent; Park, Hyokeun; Duan, Yuanyuan; Huang, Pingbo
Abstract : Protein complexes were captured by antibody modified agarose microbeads and detected by corresponding fluorophore-labeled antibodies. This assay is simple and highly sensitive for studying protein–protein interactions in rare cells. Abstract : For studying protein–protein interactions (PPIs) in general, a powerful and commonly used technique is conventional coimmunoprecipitation (co-IP/pulldown) followed by western blotting. However, the technique does not provide precise information regarding the kinetics and stoichiometry of PPIs. Another drawback is that the sensitivity of conventional co-IP is not suitable for examining PPIs in rare cells such as sensory hair cells, circulating tumor cells, embryonic stem cells, and subsets of immune cells. The current single-molecule pulldown (SiMPull) assay can potentially be used for studying PPIs in rare cells but its wide application is hindered by the high technical barrier and time consumption. We report an innovative, agarose microbead-based approach for SiMPull. We used commercially available, pre-surface-functionalized agarose microbeads to capture the protein of interest together with its binding partners specifically from cell extracts and observed these interactions under a microscope at the single-molecule level. Relative to the original method, microbead-based SiMPull is considerably faster, easier to use, and more reproducible and yet provides similar sensitivity and signal-to-background ratio; specifically, with the new method, sample-preparation time is substantially decreased (from ∼10 to ∼3 h). These crucial features should facilitate wide application of the powerful and versatile SiMPull method in common biological and clinical laboratories. Notably, by exploiting the simplicity and ultrahigh sensitivity of microbead-based SiMPull, we used the method in the study of rare auditory hair cells and γδ T cells for the first time.